Relationship Between Hope, Religiusity, Social Support, Resiliency And Subjective Well Being - Munawaroh, Eem; Muslikah, Muslikah; Suharso, Suharso; Rosdiana, Gesti (Universitas Muhammadiyah Metro, 2017)
This study aims to examine a relationship between hope, religiosity, social support, resilience and subjective well being of 455 bidik misi students University Negeri Semarang.. The research method used was correlation with random sampling as sampling technique. The data was collected by 5 scale they are hope scales using the expectation scale for adult cognitive models from Snyder, social support scales using multidimensional scales of perceived social support, subjective scales using oxford happines inventory, resilience scales using resilience scales from Reivich and Sheite, whereas religiosity was measured using the scale of religiosity. To analyze the relationship, correlational product of moment parson is used. The results showed that the correlation between subjective well being and hope outcome was 0.155, the correlation between subjective wellbeing and religiosity was 0.148, correlation between subjective well being and social performance was 0.148, Correlation between subjective well being and resilience was 0.473, and there are simultaneous influence of hope, social support, religiosity and resilience, to subjective well-being. The conclusion of this study was hope, religiosity, social support, and resilience is a predictor of subjective well being.